Effect of Cylinder Size on the Modulus of Elasticity and Compressive Strength of Concrete from Static and Dynamic Tests - Byung Jae Lee; Seong-Hoon Kee; Taekeun Oh; Yun-Yong Kim (Advances in Materials Science and Engineering)
The primary objective of this study is to investigate the effects of cylinder size (150 by 300 mm and 100 by 200 mm) on empirical equations that relate static elastic moduli and compressive strength and static and dynamic elastic moduli of concrete. For the purposes, two sets of one hundred and twenty concrete cylinders, 150 by 300 mm and 100 by 200 mm, were prepared from three different mixtures with target compressive strengths of 30, 35, and 40 MPa. Static and dynamic tests were performed at 4, 7, 14, and 28 days to evaluate compressive strength and static and dynamic moduli of cylinders. The effects of the two different cylinder sizes were investigated through experiments in this study and database collected from the literature. For normal strength concrete (≤40 MPa), the two different cylinder sizes do not result in significant differences in test results including experimental variability, compressive strength, and static and dynamic elastic moduli. However, it was observed that the size effect became substantial in high strength concrete greater than 40 MPa. Therefore, special care is still needed to compare the static and dynamic properties of high strength concrete from the two different cylinder sizes.